Способ изготовления порошковых изделий - Мельников А. Г. Александр Григорьевич; Кульков С. Н. Сергей Николаевич; Королев П. В. Петр Васильевич; Саблина Т. Ю. Татьяна Юрьевна; Савченко Н. Л. Николай Леонидович; Гнюсов С. Ф. Сергей Фёдорович
опубл. 10.01.08